2004
DOI: 10.1109/lpt.2004.831559
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Temperature Measurement of an Optical Fiber Submitted to Electric Arc Discharges

Abstract: Type S thermocouples were assembled in situ by applying high intensity electric arc discharges to the contact junction of two platinum (Pt) and Pt-10% rhodium (Pt-10% Rh) wires, inserted on a silica capillary. The electrically insulated thermocouples built in this way were afterwards employed to estimate the temperature of an optical fiber subjected to arc discharges. For typical values of the arc discharge parameters used to arc-induce long-period fiber gratings (electric current = 9 mA and arc duration = 1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…Recently, based on blackbody radiation, we estimated a value of (1400 Ϯ 50)°C for the fiber temperature [5]. In a previous work carried out using electrically insulated thermocouples [6], a value of ϳ1320°C was obtained for the temperature attained by an optical fiber during an arc discharge. In that approach, the basic requirements were as to guarantee that the arc discharge remained unperturbed and that the temperature sensor had dimensions comparable to those of an optical fiber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, based on blackbody radiation, we estimated a value of (1400 Ϯ 50)°C for the fiber temperature [5]. In a previous work carried out using electrically insulated thermocouples [6], a value of ϳ1320°C was obtained for the temperature attained by an optical fiber during an arc discharge. In that approach, the basic requirements were as to guarantee that the arc discharge remained unperturbed and that the temperature sensor had dimensions comparable to those of an optical fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, based on the new equations for the temperature dependence of the thermal conductivity of the platinum-rhodium alloys, we re-evaluated the results obtained in Ref. 6. Also, we present for the first time details on the computer simulations and the temperature dependence of all physical parameters used in the calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Fernandez et al [23] have demonstrated that LPGs written in pure-silica-core fibers using the electric-arc technique possess high resistance to γ -radiation. We have recently estimated the temperature distribution in an optical fiber submitted to an electric arc discharge [24]. Finally, we have also shown that the increase of the electric current leads to an increase of the strain sensitivity of arc-induced LPGs [25].…”
Section: Introductionmentioning
confidence: 91%
“…The formation of LPGs in germanium-doped fibers with no applied tension and for high currents (10-16 mÅ) and short duration times has also been attributed to this same mechanism [7,10]. However, assuming that the diffusion coefficient of Ge is D < 5.9 × 10 −16 m 2 ·s −1 [37] and for a fiber temperature of 1350 • C [24] a diffusion length of L < 0.03 µm is obtained for an exposure time of 1 s. The estimated refractive index change is on the order of 10 −5 , not considering the change due to waveguide modulation.…”
Section: Mechanisms Of Arc-induced Lpgsmentioning
confidence: 99%
See 1 more Smart Citation